2015
DOI: 10.2174/1874205x01509010053
|View full text |Cite
|
Sign up to set email alerts
|

Validation Study of the Mini-Mental State Examination in Urdu Language for Pakistani Population

Abstract: Validation study of the Mini-Mental State Examination in Urdu language for Pakistani populationObjective: This study was conducted primarily to validate and determine the optimal cutoff score in the diagnosis of dementia among Pakistani’s and study the effects of gender and education on the MMSE performance in our population.Methods: Four hundred participants took part in the study. Patient with dementia recruited from five major hospitals from Pakistan. The MMSE was translated into Urdu. Results: There wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…These include spatial and temporal orientation, immediate memory, attention/concentration, delayed recall, and language [15]. The Urdu translation of MMSE has previously been validated, and a cut-off value of 24 was found to maximize sensitivity and specificity (69% and 93%, respectively) when subjects of all education levels were collectively considered [16]. Therefore, patients with scores 23 or below out of 30 were considered cognitively impaired.…”
Section: Methodsmentioning
confidence: 99%
“…These include spatial and temporal orientation, immediate memory, attention/concentration, delayed recall, and language [15]. The Urdu translation of MMSE has previously been validated, and a cut-off value of 24 was found to maximize sensitivity and specificity (69% and 93%, respectively) when subjects of all education levels were collectively considered [16]. Therefore, patients with scores 23 or below out of 30 were considered cognitively impaired.…”
Section: Methodsmentioning
confidence: 99%
“…The MMSE Urdu had been translated using the back-translation method by researchers fluent in both English and Urdu for a Pakistani population. 42 It was administered to 400 participants with varied literacy: 100 with dementia and 300 healthy controls. 42 That study, which was the first validation study of the MMSE Urdu Assessing cultural adaptation of cognitive tests in Pakistan, found the MMSE Urdu to be a reliable and valid cognitive test in the screening of dementia in a Pakistani Urdu-speaking population.…”
Section: Mmse Urdumentioning
confidence: 99%
“…42 It was administered to 400 participants with varied literacy: 100 with dementia and 300 healthy controls. 42 That study, which was the first validation study of the MMSE Urdu Assessing cultural adaptation of cognitive tests in Pakistan, found the MMSE Urdu to be a reliable and valid cognitive test in the screening of dementia in a Pakistani Urdu-speaking population. We contacted the corresponding author of the MMSE Urdu to acquire their version of the test, the original English version they translated and culturally adapted, and the publication on their MMSE Urdu's psychometric validation.…”
Section: Mmse Urdumentioning
confidence: 99%
“…Максимальное количество баллов -30, ре-зультат <24 баллов указывает на наличие когнитивных проблем, 18-23 -среднее значение нарушений, 0-17 -серьезное снижение когнитивных функций. Чувствительность теста составляет 84 %, специфич-ность -80 % [17,58]. Шкала MMSE позволяет вы-явить способность пациента правильно соблюдать ре-комендации врача как при подготовке, так и во время лечения.…”
unclassified
“…7 Colorectal КОЛОПРОКТОЛОГИЯ 2' 2017 О б з о р л и т е р а т у р ы <1 -низкий риск. Шкала была валидирована в про-спективных исследованиях, проведенных в 1987, 1994 и 2014 гг., в которых также показана зависимость риска смертности от совокупности количества и тяжести коморбидной патологии, когда возраст являлся пре-диктором, влияющим на прогноз [58][59][60][61].…”
unclassified